Creation and evolution of European economic and monetary union: Lessons for Asian economic integration - Muthurangam Subramanian; Farhad Taghizadeh-Hesary; Chul Ju Kim (Asian Development Bank Institute (ADBI), 2020)
This paper reviews the creation and evolution of the European Economic Monetary Union (EEMU) and discusses the insights and perspectives of the key lessons for Asian economic integration utilizing an extensive review of the literature method. In order to implement a common monetary and economic policy for the European Union (EU), the EEMU was created as a replacement for the European Monetary System. The organization of the EEMU was designed to support sustainable economic growth and high job creation through appropriate economic and monetary policy making measures. These objectives of the EEMU can be accomplished by achieving price stability in the region through specific monetary policy implementation, coordinating with the member countries in regard to economic policies, and ensuring smooth operation of a single market in the region. Two decades of history confirm the stability of the euro as a single currency in the region and it is seen as a great achievement of the EEMU. Also, the EEMU and the European Central Bank have been successful in maintaining inflation at a lower level. Europe succeeded in reaching the level of a deeper integration mainly because of its strong vision for a united Europe, European economic and political stability, and the creation of economic and monetary institutions such as the EEMU. But, as of now, such features are not present in the Asian region. Also, despite having benefited from global trade liberalization, Asia may not strictly follow the path of European integration. However, several key lessons, including the integration process of the European Union and the experiences of the EEMU, can be taken with a view to creating an exclusive model for reaping the full benefits of Asian economic integration.
Keywords: F10; F15; F33; 330; European Union; European Economic Monetary Union; euro; Asian economic integration; regional integration